Functional amyloids promote retention of public goods in bacteria - Bruce, J; West, S; Griffin, A (Royal Society, The, 2019)
The growth and virulence of bacteria depends upon a number of factors that are secreted into the environment. These factors can diffuse away from the producing cells, to be either lost or used by cells that do not produce them (cheats). Mechanisms that act to reduce the loss of secreted factors through diffusion are expected to be favoured. One such mechanism may be the production of Fap fibrils, needle-like fibres on the cell surface observed in P. aeruginosa, which can transiently bind several secreted metabolites produced by cells. We test whether Fap fibrils help retain a secreted factor, the iron-scavenging molecule pyoverdine, and hence reduce the potential for exploitation by non-producing, cheating cells. We found that: (i) wild-type cells retain more iron-chelating metabolites than fibril non-producers; (ii) purified Fap fibrils can prevent the loss of the iron-chelators PQS (Pseudomonas quinolone signal) and pyoverdine; and (iii) pyoverdine non-producers have higher fitness in competition with fibril non-producers than with wild-type cells. Our results suggest that by limiting the loss of a costly public good, Fap fibrils may play an important role in stabilizing cooperative production of secreted factors.